An unusual presentation of extragenital lichen sclerosus-An extensive keratotic variant - Mario Magaña; Carol Estefania Márquez‐Maldonado (Wiley, 2024)
Abstract In this case report, we outline a case of a 71‐year‐old woman who presented to the dermatology clinic with a history of keratotic and atrophic warty‐like plaques on her lower limbs, which limited the movements in her right lower extremity. A skin radial biopsy of one of the plaques was performed and the diagnosis of extragenital lichen sclerosus (ELS) was established. She underwent an anogenital exam and fortunately, lesions were not found. The patient in this case showed an unusual variant of ELS.